Status Mental Emosional Anak Berdasarkan Pola Asuh Orangtua Di Kampung Kelapa Kabupaten Tangerang - Dorsinta Siallagan; Reni Nofita; Chairunnisa Minarni Alamysah (Jurnal Kesehatan, 2023)
Parenting patterns affect the mental and emotional status of children. Democratic parenting makes children grow up independently, while children who are raised undemocraticly cause children to tend to be timid, selfish and have no respect for others. Purpose: to determine the relationship between parenting and the emotional mental status of children in Dandang Village, Tangerang Regency. Method: This research method is descriptive analysis with a cross sectional study design. The research location was conducted in Kelapa Village, Tangerang Regency. The sample in this study was 47 respondents using saturated sampling. Data analysis using chi square. Result: 34 (72.3%) respondents with normal emotional mental status, 32 (68.1%) respondents gave democratic parenting, and the significance value of p value was 0.000 <0.05.Conclusion: here is a significant relationship between parenting patterns and children's emotional mental status with a p value of 0.000. Suggestion: Parents provide good parenting for children’s mental and emotional development, take parenting classes